The effect of filled pauses on the processing of the surface form and the establishment of causal connections during the comprehension of spoken expository discourse - Yomha Cevasco, Jazmin (2016)
The purpose of this study was to examine the effect of filled pauses (uh) on the verification of words and the establishment of causal connections during the comprehension of spoken expository discourse. With this aim, we asked Spanish-speaking students to listen to excerpts of interviews with writers, and to perform a word-verification task and a question-answering task on causal connectivity. There were two versions of the excerpts: filled pause present and filled pause absent. Results indicated that filled pauses increased verification times for words that preceded them, but did not make a difference on response times to questions on causal connectivity. The results suggest that, as signals of delay, filled pauses create a break with surface information, but they do not have the same effect on the establishment of meaningful connections.